A Colour Analysis Tool for Product Appearance - Tsai, Cheng-Min; Gao, Xue (E3S web of conferences, 2020)
This study proposes an image colour analysis tool that could help graphic/product designers to understand colour distribution and colour appearance of a series product. The analysis method is in accordance with the CIE Lab uniform colour space created by the International Commission on Illumination (CIE) in 1976. Based on the analysis method used in a previous study of the oil paintings, 370 oil paintings were analysed. The results demonstrated that using simple colour difference formula could reveal the images’ numerical colour distribution (Tsai, 2019). The focus of this study is twofold: to understand the colour appearance of product design and to check the rationality and reliability of the analysis tool. The analysis tool this study proposes could also be useful in providing the product designers with easy analysis and understanding of the colour distribution of images.